1998
DOI: 10.1002/hep.510270107
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of hepatorenal syndrome by prolonged administration of ornipressin and plasma volume expansion

Abstract: Hepatorenal syndrome is caused by a marked vasoconstriction of the renal circulation. It is suggested that the renal vasoconstriction is related to an overactivity of vasoconstrictor systems secondary to a vasodilation of the arterial circulation that causes a reduction in effective arterial blood volume. To test this hypothesis, 16 cirrhotic patients with hepatorenal syndrome were treated with a combination of ornipressin, a potent vasoconstrictor agent, and plasma volume expansion with albumin to improve eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
175
2
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(189 citation statements)
references
References 42 publications
8
175
2
4
Order By: Relevance
“…The rate of adverse events leading to withdrawal in this study (5%) is consistent with findings in the literature and is reported to be lower with terlipressin as compared with vasopressin and other vasopressin analogues. [37][38][39] In summary, terlipressin plus albumin is superior to placebo for reversal of type 1 HRS and produces a significant decrease in SCr compared with placebo and albumin. Administration of albumin by itself also had a modest salutary effect and reversed HRS in 13% of cases.…”
Section: Discussionmentioning
confidence: 90%
“…The rate of adverse events leading to withdrawal in this study (5%) is consistent with findings in the literature and is reported to be lower with terlipressin as compared with vasopressin and other vasopressin analogues. [37][38][39] In summary, terlipressin plus albumin is superior to placebo for reversal of type 1 HRS and produces a significant decrease in SCr compared with placebo and albumin. Administration of albumin by itself also had a modest salutary effect and reversed HRS in 13% of cases.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies using ornipressin over fixed periods of 4 hours, 11 3 days, or 15 days 16 provided the pathophysiological basis for the present investigation: It has been suggested that ornipressin ameliorates peripheral arterial vasodilation and thereby decreases plasma renin activity, aldosterone release, and sympathetic activity. Consecutively, an increase of renal plasma flow and glomerular filtration rate can be observed.…”
Section: Discussionmentioning
confidence: 92%
“…13 Compatible with these considerations, 2 case reports suggested a therapeutic potential of ornipressin infusion in patients with HRS, 14,15 and recently, in a group of patients with HRS type 1 or type 2, prolonged infusion of ornipressin in combination with plasma volume expansion reverted HRS. 16 Differentiation of 2 types of HRS has been proposed 17 : HRS type 1 is characterized by a more than 2-fold increase of serum creatinine to concentrations above 2 mg/100 mL or a decrease of creatinine clearance below 20 mL/min within 2 weeks. HRS type 2 is characterized by serum creatinine levels elevated above 1.5 mg/100 mL or creatinine clearance below 40 mL/min without rapid deterioration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…46 Eight patients were enrolled in a non-randomized study and received ornipressin (2 IU/ h) and intravenous albumin (1 g/kg at day 1 and then 20-40 g per day). 47 Ornipressin administration was scheduled for 15 days. However, during the first week of the study, treatment had to be discontinued in four patients.…”
Section: Ornipressinmentioning
confidence: 99%